2021
DOI: 10.1128/spectrum.01588-21
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-Mediated Lung Injury Both via TLR2-Dependent Production of IL-1α and IL-12 p40, and TLR2-Independent CARDS Toxin after Mycoplasma pneumoniae Infection in Mice

Abstract: Although Mp-induced pneumonia is usually a self-limiting disease, refractory life-threatening pneumonia is often induced. In addition, the development of alternative therapeutic strategies for Mp is expected because of the emergence of antibiotic-resistant Mp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Higher proportions of neutrophils were detected in the BALF of SMPP patients ( 14 ). In mice, neutrophils have been proved to mediate lung injury during the infection of MP ( 30 ). In a previous study, we found that both cell damage and neutrophils contribute to MP infection and cytokine expression ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Higher proportions of neutrophils were detected in the BALF of SMPP patients ( 14 ). In mice, neutrophils have been proved to mediate lung injury during the infection of MP ( 30 ). In a previous study, we found that both cell damage and neutrophils contribute to MP infection and cytokine expression ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil infiltration is generally recognized as one of the features of Mp pneumonia. While neutrophils are not essential for the clearance of Mp from the lungs [ 9 , 10 ], in the situation of “hyperinflammation,” excessive accumulation of neutrophils might cause lung injury by releasing myeloperoxidase (MPO) and proteases [ 10 , 25 ]. To investigate whether AOFE reduces inflammation in Mp pneumonia, we first examined if the administration of AOFE had an adverse effect on mouse health by feeding mice daily with different doses of AOFE for 10 days.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical studies have shown that increased accumulations of neutrophils and lymphocytes are associated with the severity of Mp pneumonia, and may contribute to the pathogenesis [ 25 , 31 ]. In an animal model of Mp pneumonia, Tamiya et al showed that depletion of neutrophils did not affect the number of Mp in the BALF, but significantly reduced tissue injury, indicating that neutrophils contribute to lung injury, but not Mp clearance [ 10 ]. Our data showed that AOFE administration significantly reduced the infiltration of neutrophils into the lungs, suggesting that lung injury may also be reduced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of neutrophil infiltration into the lungs in Mycoplasma pneumoniae pneumonia involves the excessive production of various inflammatory cytokines and chemokines. 29 Thus, we can infer that Mycoplasma pneumoniae infection impacts the increase of HBP. Further, we have adjusted the logistic regression models for probable pathogens to account for the direct microbial damage to the respiratory tract.…”
Section: Discussionmentioning
confidence: 97%